Clinical Characteristics, Diagnosis, and Treatment of Central Nervous System Candidiasis: A Systematic Review of 418 Cases - Guilherme Diogo Silva; Mariane Taborda; Wdson Luis Lima Kruschewsky; Leonardo Torioni; Mariane Cappellini Stricagnolo; Bernardo Ferreira Camilo; Isadora Campos de Sousa Abreu; Isabela Cristina Oliveira Silva; Nadine Correia Silva Santos; Gabriel Diniz Resende; Marcello Mihailenko Chaves Magri; Adriana Satie Gonçalves Kono Magri; et al. (Mycopathologia, 2026)
Background Central nervous system (CNS) candidiasis is a rare but life-threatening complication of invasive candidiasis. However, current knowledge derives mainly from isolated case reports, and no comprehensive synthesis has been previously performed. Methods We conducted a systematic review of published cases of CNS candidiasis. PubMed and Embase were searched without language or date restrictions. Eligible cases required microbiological or histopathological confirmation of Candida spp. and evidence of CNS involvement on cerebrospinal fluid (CSF) analysis or neuroimaging. Demographic, clinical, radiological, laboratory, therapeutic, and outcome data were extracted. We compared mortality and non-mortality groups, paediatric and adult patients, and diagnostic periods. Results We identified 418 patients reported between 1945 and 2024 (median age, 21 years [IQR 0–46]; 62% male). Prior antibiotic use (53%), intravascular catheterization (31%), and neurosurgery (22%) were common risk factors. Neuroimaging was abnormal in 87% of cases, and cerebrospinal fluid was abnormal in 96%, typically showing neutrophilic or lymphocytic pleocytosis and low glucose. Nearly half of cases were pediatric (41% of very-low-birth-weight neonates), who more often had healthcare-associated risk factors and less often immunosuppressive conditions. Overall mortality was 35%, mostly within 30 days; older age was associated with higher mortality, whereas combination antifungal therapy and more recent diagnostic periods were associated with lower mortality in multivariate analysis. Over time, immunosuppression, non-albicans Candida species, and antifungal use increased, while autopsy-based diagnoses and mortality declined. Conclusion CNS candidiasis is a rare but severe infection with challenging diagnosis and high mortality, emphasizing the importance of early recognition and appropriate antifungal therapy.